Production and Quality Evaluation of Probiotic Malunggay (Moringa oleifera Lam.) Ice Cream - Gisulga, Jessa B. (JPAIR Multidisciplinary Research, 2018)
The study aimed to produce probiotic malunggay ice cream. It further aimed to determine and assess the effects of the probiotic malunggay on the sensory quality of the product, its physico-chemical properties, stability, consumer reaction and the cost of production. The research study used a 3 x 3 factorial experimental type of research in Randomized Complete Block Design (RCBD) with two (2) replicates and with three (3) levels of malunggay, namely, 0%, 15%, and 30% (w/v) and three (3) levels of probiotic cultures 0%, 20%, and 40% (w/v). The findings of the study revealed that sensory evaluation showed that only malunggay was significantly affected by the acceptability of the aforementioned sensory evaluation. When Malunggay was subjected to sensory evaluation, High levels of malunggay elicit low acceptability on its color, taste, flavor, and texture. In terms of pH, and TA of the probiotic malunggay, when it was made into ice cream, such was affected by the levels of the probiotic culture, increased levels of probiotic culture correspond to a higher pH and TA values thus, increased levels of probiotic culture could further increase the initial microbial count of the probiotics in the product. Further studies may be conducted to confirm the storage stability of the probiotic microorganisms over an extended period of frozen storage.
Keywords: Malunggay; Probiotic; Production; Ice Cream; Philippines